Techno-economic assessment of a novel integrated system of mechanical-biological treatment and valorisation of residual municipal solid waste into hydrogen: a case study in the UK - Ng, Kok Siew; Phan, Anh N.; Lacovidou, Eleni; Wan Ab Karim Ghani, Wan Azlina (Elsevier BV, 2021)
Resources embedded in the waste streams are often not properly recovered and are mostly ended up in landfills or only recovered as energy via energy-from-waste (EfW) facilities. Innovative resource recovery from waste strategies are urgently needed to maximise resource efficiency, divert waste from landfills and reduce reliance on EfW. This study proposes a novel mechanical-biological treatment with valorisation concept (MBT-v) that combines material recovery and fuel production, as alternatives to EfW for residual municipal solid waste (MSW) treatment. The polygeneration feature exhibited by the MBT-v system enhances resource efficiency and product diversification. The proposed MBT-v system involves valorisation of rejected materials from MBT into hydrogen by incorporating an additional gasification system. A comprehensive techno economic assessment is conducted for the proposed MBT-v system and compared against a conventional MBT. The results reveal that the conventional MBT strongly relies on gate fees to be economically viable while it is heavily impacted by the rejects disposal cost. The analysis also shows that higher economic potential (36.4 M£/y) for MBT-v can be obtained compared to that of conventional MBT (3.4 M£/y) for a 100 kt/y residual MSW system. The minimum hydrogen selling price (MHSP) from the Gasification-H2 system is estimated to be at 3.4 £/kg (28.3 £/GJ), with potential for further reduction through upscaling the facility. This study concludes that producing high value product such as hydrogen (with the current assumed market price of hydrogen of 10 £/kg) can significantly improve the economic performance and minimise financial instability of the facilities. It is recommended that the scale and optimal configuration of MBT-v to be designed based on local conditions.